Interactive effect of thermal and hypoxia on largemouth bass (Micropterus salmoides) gill and liver: Aggravation of oxidative stress, inhibition of immunity and promotion of cell apoptosis. Issue 98 (March 2020) - Sun, Jun-Long; Zhao, Liu-Lan; Liao, Lei; Tang, Xiao-Hong; Cui, Can; Liu, Qiao; He, Kuo; Ma, Ji-Deng; Jin, Long; Yan, Tao; Zhou, Jian; Yang, Song
Abstract: High temperatures and low oxygen in aquatic environments, such as intensive aquaculture or in natural watersheds, inevitably cause stress in fish. Fish are exposed to high temperatures during the summer, which exacerbates hypoxia. Hypoxia (1.2 ± 0.2 mg/L) under 20 °C (20 HG) and 26 °C (26 HG) was simulated to induce stress in largemouth bass ( Micropterus salmoides ). Related enzymes and genes involved in antioxidant, immune, and apoptotic responses were selected to explore the interactive effects of temperature and hypoxia on largemouth bass. The results showed that malondialdehyde (MDA) levels in plasma, gill, and liver increased in the 26 HG ( p  <  0.05 ). Liver superoxide dismutase (SOD) activity increased in the 26 HG. Peak SOD ( SOD1, SOD2, SOD3a, and SOD3b ), CAT, and GSH-Px mRNA levels in the gill and liver were observed at 12–24 h of stress. The levels of gill and liver total antioxidant capacity, catalase (CAT), glutathione peroxidase (GSH-Px) activities and other enzyme activities and genes in the 26 HG were higher than those in the 20 HG ( p  <  0.05 ). The gill and liver acid phosphatase and alkaline phosphatase activities increased with time in the 26 HG ( p  <  0.05 ), while gill and liver lysozyme activities in the 26 HG were lower than those in the 20 HG ( p  <  0.05 ). Tumor necrosis factor-α mRNA level was upregulated in the gill and downregulated in the liver at 24 h in the 26 HG. Interleukin ( IL)-1β and IL- 8 mRNA levels were upregulated in the gill and liver in the 26 HG at 24 h, whereas IL- 15 mRNA level was downregulated in the 26 HG at 12 h. Transforming growth factor-β1 mRNA level was upregulated in the gill in the 20 HG at 24 h, but downregulated in gill and liver in the 26 HG at 24 h. Similarly, IL-10, Hepcidin-1, and Hepcidin-2 showed lower expression levels in the 26 HG. Gill and liver caspase-3 activities were higher in the 26 HG ( p  <  0.05 ), and gill caspase-3 activity was higher than that in the liver. The mRNA levels of proapoptotic genes ( caspase-3, caspase-8, and caspase-9 ) were higher in the 26 HG. The present study demonstrates the interactive effects of temperature and hypoxia on stress in largemouth bass gill and liver. These results will be helpful to understand the mechanisms of stress induced by temperature and hypoxia in fish and provide a theoretical basis for aquaculture management. Highlights: High temperature aggravates oxidative stress in gill and liver under acute hypoxia. Immune response in gill and liver is inhibited under high temperature and hypoxia. Combined effect of heat and hypoxia promotes gill and liver cell apoptosis.